Effect of scanning speed on microstructure profile of selective laser melted stainless steel 316L - Mohammad Azlan Aripin,; Zainuddin Sajuri,; Nashrah Hani Jamadon,; Intan Fadhlina Mohamed,; Syarif Junaidi,; Ahmad Muhammad Aziz,; Mohd Rhafiq Mazlan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The selective laser melting (SLM) manufacturing process is currently gaining interest from various industries due to its ability to produce complex and hollow shapes. Processing parameters have been manipulated to obtain the best mechanical performance. However, the long production time remains the only major disadvantage compared to injection moulding. Production time can be decreased by increasing the scanning speed. This paper intends to investigate the effects of increasing scanning speed on the microstructural properties of SLM-produced stainless steel 316.Alteration of scanning speed directly affects the energy density and the thermal history of the parts. Twoscanning speeds are used in the experiment with speed 750 mms-1 (V750) as the current default speed and 1400 mms-1 (V1400) for faster production time. The phases generated from each process were identified using the XRD test. Thedifference between austenite and ferrite in both samples is not distinct. High scanning speed results in slightlyhigher ferrite at 8.57% as compared to 6.03% for low scanning speed. It also yields lower austenite at 91.43% ascompared to 93.97% at 750 mms-1. The microstructure observation reveals V750 has deeper penetration andthinner melt pools. The higher energy density is related to the keyhole porosities found in the optical microscopy ofV750 and thinner melt pools have enabled non-diffusion porosities at the side of melt pools. These findings willultimately help the learning community to optimize the SLM processing parameters to achieve desired microstructuralproperties of 316L